Pedagogical Approaches to Enhancing Fine Motor Skills in Early Childhood through Play-Based Activities - Faziras Nur Amira; Rozman Ab. Kadir (Universitas Lancang Kuning, 2025)
Early childhood is a critical period of rapid physical and mental development, often referred to as the